The Study of Derrida’s Deconstruction in the Short Story “Kembang Dewaretna” by Yanusa Nugroho - Rauf, Ramis; Ulya, Afriani (IAIN KENDARI, 2025)
This paper reveals the main problem regarding the author's efforts in presenting the reversal of the hierarchy of the character Danaraja who experiences defeat in the short story